THE EFFECT OF ENDORSER CREDIBILITY, TOWARD ADVERTISEMENT ATTITUDE, TOWARD BRAND ATTITUDE AND BRAND CREDIBILITY ON PURCHASE INTENTION OF SMARTFREN CARD PRODUCTS - Azmil Chusnaini; Reizano Amri Rasyid; C Candraningrat (JMM17 : Jurnal Ilmu ekonomi dan manajemen, 2021)
This study examines the causal relationship between endorser's credibility, attitudes towards brands, brand credibility, attitude towards advertising and purchase intention of the smartfren mobile card adopt the celebrity endorsement strategy. Meanwhile, attitudes towards advertising were tested as second-order constructs of the three proposed models. Smartfren recently used Atta Halilintar and Tiara Idol as celebrity endorsers of brand products in every ad serving. Examine whether have a celebrity that the public likes for supporting advertising will improve brand attitude, brand credibility, attitude towards fish, and intention to buy smartfren products. Methodology design conceptual model approach developed based on existing literature. The models are validated through a quantitative approach, analyzed using regression analysis with SEM. Technique sampling in this study using nonprobability sampling with using a snowball sampling approach. This research is a development of Previous research that tested the variables of endorser credibility, attitudes towards the product, brand credibility against purchase intentions.